2019
DOI: 10.1002/jbt.22322
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mechanism of free Nε‐(carboxymethyl)lysine‐induced toxic injury in mice

Abstract: Nε‐(carboxymethyl)lysine (CML), which is a compound produced when food is processed, has aroused concern in recent years because of its potentially dangerous effects. This study aimed to investigate the mechanism of free CML‐induced toxic injury in mice. The inflammatory cytokine tumor necrosis factor‐α, transforming growth factor‐β, vascular cell adhesion molecule‐1 mRNA expression levels of CML‐infected mice liver and kidney tissues significantly increased. While CML receptor—receptor for advanced glycation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It engages different ligands, not only AGEs, but also the amyloid β peptide, S100/calgranulin protein, HMGB1, and LPS, ultimately leading to an alteration in gene expression [15][16][17][18]. Recent studies have shown that Ne(carboxymethyl)lysine (CML) adducts of proteins, the most frequent type of AGEs found in vivo, interact with RAGE to activate signal transduction pathways [19,20], ultimately leading to the expression of proinflammatory genes [21]. Thus, it has been shown that treating cells with AGEs produces a rapid increase in both mRNA and protein levels of RAGE [22] which is suppressed after pretreatment with the anti-RAGE antibody [23].…”
Section: Advanced Glycation Endproducts Drive Cell Signaling and Inflmentioning
confidence: 99%
“…It engages different ligands, not only AGEs, but also the amyloid β peptide, S100/calgranulin protein, HMGB1, and LPS, ultimately leading to an alteration in gene expression [15][16][17][18]. Recent studies have shown that Ne(carboxymethyl)lysine (CML) adducts of proteins, the most frequent type of AGEs found in vivo, interact with RAGE to activate signal transduction pathways [19,20], ultimately leading to the expression of proinflammatory genes [21]. Thus, it has been shown that treating cells with AGEs produces a rapid increase in both mRNA and protein levels of RAGE [22] which is suppressed after pretreatment with the anti-RAGE antibody [23].…”
Section: Advanced Glycation Endproducts Drive Cell Signaling and Inflmentioning
confidence: 99%
“…The anti-inflammatory activity of CIGB-258 might have originated partially from the structural and functional stabilization of HDLs against CML-induced glycation of HDLs and modification [ 21 ]. Although the CML is a relatively stable advanced glycated end (AGE) product, many previous papers suggested its neurotoxicity and oral toxicity [ 22 , 23 , 24 ]. The CML can bind to tissue proteins [ 25 ] and accumulate in animal tissues after 12 weeks of oral administration via glycoxidation and lipid peroxidation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies indicated that AGEs including CML induced ROS production, resulting in oxidative stress damage in cells. 29,30 In order to investigate the effects of Pn3G5G and/or CML on the oxidative stress, we detected the ROS level and malondialdehyde (MDA) concentration (a marker of lipid peroxidation (LPO)) in Neuro-2a cells. As displayed in Fig.…”
Section: Effect Of Pn3g5g On Cml-induced Oxidative Stress In Neuro-2a...mentioning
confidence: 99%